PENILE FRACTURE; ETIOLOGY AND MANAGEMENT - Muhammad Akram Malik; M. Tahir Bashir (Journal of University Medical & Dental College, 1970)
ABSTRACT Introduction: Penile fracture is a rare urological emergency that occurs almost exclusively due to blunt trauma on erect penis. Trauma causes tear in tunica albugenia. The diagnosis is straight forward and based on classical history of snap sound, pain, detumescence, swelling and deformity. Early surgical intervention gives good cosmetic and functional outcome. Material and Methods: This retrospective study was conducted between Jan 2001 to Dec 2010. Patients presented with penile fracture were included in the study. All patients were managed by sub-coronal incision and repair of tunica albugenia tear with prolin (Polypropylene) 3/0. Results: Thirteen patient of penile fracture with age range of 17-48 years (mean=34 years) presented to us. Ninety two percent of patients were below 40 years. Eighty four percent suffered injury during coitus. Almost all patients experienced cracking sound followed by pain, swelling, detumescence and deformity. Interval between trauma and presentation varied from 06 hours to 14 days (mean=60 hours). Twelve patients were managed surgically and 01 managed conservatively. Painful coitus was the only complication reported. Majority of patients (53.84%) experience successful intercourse with in 04 weeks. None of the patients reported impotence. Conclusion: Penile fracture is a rare urological emergency which requires early surgical intervention for better outcome and minimal rate of complications.